2019
DOI: 10.1016/j.avsg.2018.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Educational Intervention on Ankle–Brachial Index Performance Among Medical Students and Fidelity Assessment at Six Months

Abstract: Background: The resting ankle-brachial index (ABI) is a clinical test to diagnose peripheral artery disease (PAD). The Wyatt's score has been proposed to assess the students' performance on ABI measurement on a healthy volunteer (HV). No study has shown that this score is sensitive to different teaching methods. In this randomized-controlled-trial, we wanted to determine whether didactic learning alone or didactic learning combined with experiential learning improve proficiency in the ABI procedure assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(19 reference statements)
0
2
0
1
Order By: Relevance
“…The other interest of simplifying the ABI measurement might be about the education of medical students and residents. Indeed, studies have demonstrated that learning how to measure ABI is challenging (34) and not sustained (35). We hypothesize that this simplified method might improve the performance of medical students and residents to perform ABI, but this remains to be studied.…”
Section: Discussionmentioning
confidence: 97%
“…The other interest of simplifying the ABI measurement might be about the education of medical students and residents. Indeed, studies have demonstrated that learning how to measure ABI is challenging (34) and not sustained (35). We hypothesize that this simplified method might improve the performance of medical students and residents to perform ABI, but this remains to be studied.…”
Section: Discussionmentioning
confidence: 97%
“…[12][13][14][15][16] En este contexto, se ha señalado que las estrategias educativas planeadas tienen un efecto positivo en el aprendizaje de los médicos en formación. [17][18][19][20][21][22][23][24][25][26] Sin embargo, dichas estrategias se realizan principalmente en el aula, lo cual puede ser de gran utilidad; pero el internado médico de pregrado es una etapa principalmente práctica donde se aprende frente al paciente de forma tutorizada por médicos de mayor experiencia, dicha actividad está sustentada por diversas teorías del aprendizaje en que son fundamentales los factores cualitativos. [27][28][29][30][31] Debido al contexto señalado y a la importancia del desarrollo de competencias útiles para el médico general mexicano, 32 el objetivo del presente estudio fue describir la entrega de guardia y la presentación de casos clínicos en el servicio de pediatría y su impacto en el aprendizaje en médicos internos de pregrado.…”
Section: Introductionunclassified
“…[12][13][14][15][16] In this context, it has been pointed out that planned educational strategies have a positive effect on the learning of physicians in training. [17][18][19][20][21][22][23][24][25][26] However, these strategies are mainly carried out in the classroom, which can be very useful; but the undergraduate medical internship is a mainly practical stage where undergraduates learn in front of the patient under the guidance of more experienced physicians, and this activity is supported by various learning theories in which qualitative factors are fundamental. [27][28][29][30][31] Due to the aforementioned context and the importance of developing useful competencies for Mexican general practitioners, 32 the objective of the present study was to describe on-call handover, and the presentation of clinical cases in the pediatric service, and its impact on learning in undergraduate medical interns.…”
Section: Introductionmentioning
confidence: 99%